Investıgatıon Of Three Dımensıonal Cranıofacıal Structure - Mirzen Arat; Meliha Rübendüz; Ayşegül Köklü; Fikret Gürbüz (Galenos Yayinevi, 1995)
The aim of this investigation is to determine longitudinally the face and head in horizontal, sagittal and vertical dimensions. Investigation was carried on PA, LS, and hand and wrist radiograms of 15 females, collected annually, followed between 10-14 ages. The annual changes of the measurements and ratios were evaluated on the PA and LS, and the relations between these and developmental changes were investigated. Resultant measurements reveal significant increments in three dimensions of skeletal measurements during the first two years. However, dental arch width and facial ratios in horizontal, sagittal and vertical dimensions displayed no changes. The relation between the skeletal development and craniofacial dimensional changes was found to be significant merely in mandibular dimensions